Perancangan Film Pendek Etika Mahasiswa Terhadap Dosen Program Studi Teknik Informatika Universitas PGRI Madiun - Yoga Prisma Yuda; Muh Nur Luthfi Azis (STIKOM Tunas Bangsa Pematangsiantar, 2019)
The use of multimedia has been used in various purposes at this time. Began to be used as an entertainment media, advertising, business and also education. The short movie is a part of multimedia. Using a short movie in educational media is very popular today. In making a short movie, it is necessary to design story concepts and techniques. In